Material estructurado y nociones lógico- matemáticas en niños de Preparatoria de la Escuela de Educación Básica Dr. Reinaldo Espinosa Aguilar de la ciudad de Loja, periodo 2023-2024 - Tapia Campoverde, Crisley Itamar (2024)
The development of logical-mathematical concepts is essential for children's well-being and progress, as these concepts form the foundation of the teaching process at higher levels and contribute to the development of thinking and intelligence, enabling them to solve problems in various areas of everyday life. Therefore, the main objective of this research was to implement structured material to contribute to the development of logical-mathematical concepts in kindergarten children at Dr. Reinaldo Espinosa Aguilar Primary School in Loja city. A mixed approach was used for the study, allowing for both quantitative and qualitative investigation and information collection. The study had a descriptive scope, enabling the collection of information on the variables and phenomena causing difficulties, as well as the collection and analysis of results from the applied instruments. The inductive-deductive methods were also used, facilitating a concrete study of the information and allowing for the analysis of results, contributing to the establishment of conclusions. The study involved 30 children, as the group was very small and the entire population was included without sampling. The EVAMAT-0 test was used as the instrument, and the diagnosis revealed that 53% of the children were in the low zone, indicating that most had difficulties distinguishing geometric figures, series, quantity-counting, and solving simple problems. After applying the activity guide, it was found to be effective, improving the percentages to 73% in the high zone. The research confirmed the effectiveness of structured material in strengthening logical-mathematical concepts and essential skills to reach high levels in the comprehensive development of children. Keywords: Mathematical competencies, quantity and counting, geometry, didactic material, problem-solving.